Incidencia del comercio justo en la calidad de vida de productores agrícolas - Moreira Basurto, Jesús Adrián (2025)
Fair Trade (FT) is presented as an alternative to the traditional commercial model, focused on ensuring fair prices, social and environmental sustainability, and economic benefits for small producers. This study aims to determine the impact of FT on the quality of life (QoL) of the members of the Corporación de Productores de Plátano Industrializadores y Comercializadores Sumita Palmita (Corpicsupal) in the canton of El Carmen, Manabí Province, Ecuador. The research adopted a quantitative approach, with a descriptive and correlational scope, under a non-experimental and cross-sectional design, applying surveys to the 70 members of Corpicsupal through validated instruments. Statistical analysis was conducted with SPSS v.25, verifying reliability with Cronbach’s Alpha and employing normality tests (Kolmogorov-Smirnov) as well as Pearson or Spearman correlations as appropriate. The statistical analysis performed with the Spearman correlation test evidenced a positive and significant correlation (ρ = 0.322) between participation in this commercial model and the well-being of producers. Although the relationship is weak, improvements in QoL were identified, such as the adoption of sustainable practices and the strengthening of human relationships. Nonetheless, challenges persist, particularly low income and limited access to technological resources. The study recommends strengthening the value chain and exploring complementary programs to enhance the benefits observed.